Sustainable Style: How Environmental Knowledge And Environmental Concern Influence Gen-Z’s Fashion Choices - Dapit Edo; Puty Febriasari; Thea Geneveva J. Jesajas (Jurnal Ekonomi, 2024)
This study investigates the factors influencing sustainable fashion behavior among Indonesian Gen Z, focusing on the roles of environmental knowledge (EK), environmental concern (EC), and attitude toward sustainabe fashion (ATT). The popularity of thrifting among Gen Z has risen, particularly in Indonesia. Thrifting offers a unique shopping experience that evokes various feelings, seen as a cost-effective solution by purchasing second-hand items that are still in good condition. Given the gap in global literature, the author selects Gen Z as the research context and subject of study. Through a comprehensive examination of sustainable fashion, this research aims to clarify the relationship between knowledge, concern, and attitude between Gen Z toward sustainable fashion. This study integrates quantitative methods, where a questionnaire survey will be distribute to respondents to gain deeper understandi ng of these issues. The results of this study indicate that both knowledge and concern jointly influence Gen Z's attitude towards sustainable fashion. Additionally, further path analysis shows that environmental concern fully mediates the relationship between knowledge and attitude. The results of data analysis reveal that environmental knowledge influences attitude toward sustainable fashion (R2=3.72) and environmental knowledge influences environmental concern (R2=0.319).The study confirms that environmental knowledge and attitudes play crucial roles in shaping sustainable fashion behaviors among Indonesian Gen Z. Enhancing environmental education and promoting sustainable fashion practices can positively influence purchase intentions and behaviors. These findings have important implications for policy makers, educators, and the fashion industry, highlighting the need for integrated efforts to foster sustainable consumption patterns.